Using Vegetative Filter Strips in Crop Fields - Reger, David L.; Devlin, Daniel L.; Barnes, Philip L. (My University, 1996)
This publication Explains the way pollutants move and the role of vegetative filter strips in reducing the amount of pollutants that leave the field.
MF2224_1996_07
Keywords: MF2224; Environment and Natural Resources; Crops; MF